Flow chart for the study selection. - Ignacio Bórquez (22477946) (2025)
Introduction In Latin America and the Caribbean (LAC) the response to substance use has primarily been abstinence-based, acute-care-oriented treatments. While harm reduction services (HRS) and interventions have expanded in LAC over the last decade, the research evidence on such programs has been sparse and disjointed. Objective This scoping review will map peer-reviewed literature on HRS and interventions in LAC, and synthesize gaps and opportunities for policy, practice, and research. Inclusion criteria Studies conducted in LAC. The HRS that will be included in the search are opioid agonist therapy, syringe services programs, drug consumption facilities, safer consumption kits, managed alcohol programs, and drug-checking services. The scoping review will consider peer-reviewed original research, including qualitative, quantitative, and mixed-methods designs. We will exclude studies addressing harms associated with nicotine or tobacco use. We included original research written in English, Spanish, Portuguese, or French published between January 2013 and December 2024. Methods We will conduct literature searches in English (PubMed, Scopus, Web of Science), Spanish, Portuguese (SciELO and BIREME), and French (BIREME). Two reviewers will independently screen the literature. Extraction of characteristics of the studies using a template in Covidence. Data on the HRS and interventions studied and implemented in LAC will be summarized and presented in tables, graphs, and a narrative summary. We will use a narrative synthesis approach to summarize implications for policy, research, and practice identified in the literature. The review was registered in Open Science Framework (https://osf.io/qya7c/), Discussion The proposed scoping review will provide valuable information regarding the current state of HRS and interventions for PWUD in LAC. This in return can help guide future research for evaluating services that are already being implemented or unveil services needed in the region. To our knowledge, this is the first scoping review to map HRS in LAC using a systematic approach. Furthermore, among the strengths of this review are: the broad number of services, countries, and time, as well as the consultation with experts and knowledge users.